Microbial bioburden of inpatient and outpatient areas beyond patient hospital rooms. (23rd August 2022) - Cadnum, Jennifer L.; Pearlmutter, Basya S.; Jencson, Annette L.; Haydar, Hanan; Hecker, Michelle T.; Ray, Amy J.; Tomas, Myreen E.; Saade, Elie A.; Donskey, Curtis J.
Abstract: Objective: To investigate the frequency of environmental contamination in hospital areas outside patient rooms and in outpatient healthcare facilities. Design: Culture survey. Setting: This study was conducted across 4 hospitals, 4 outpatient clinics, and 1 surgery center. Methods: We conducted 3 point-prevalence culture surveys for methicillin-resistant Staphylococcus aureus, vancomycin-resistant enterococci, Clostridioides difficile, Candida spp, and gram-negative bacilli including Enterobacteriaceae, Pseudomonas aeruginosa, Acinetobacter baumanii, and Stenotrophomonas maltophilia in each facility. In hospitals, high-touch surfaces were sampled from radiology, physical therapy, and mobile equipment and in emergency departments, waiting rooms, clinics, and endoscopy facilities. In outpatient facilities, surfaces were sampled in exam rooms including patient and provider areas, patient bathrooms, and waiting rooms and from portable equipment. Fluorescent markers were placed on high-touch surfaces and removal was assessed 1 day later. Results: In the hospitals, 110 (9.4%) of 1, 195 sites were positive for 1 or more bacterial pathogens (range, 5.3%–13.7% for the 4 hospitals) and 70 (5.9%) were positive for Candida spp (range, 3.7%–5.9%). In outpatient facilities, 31 of 485 (6.4%) sites were positive for 1 or more bacterial pathogens (range, 2% to 14.4% for the 5 outpatient facilities) and 50 (10.3%) were positive for Candida spp (range, 3.9%–23.3%). Fluorescent markers had been removed from 33% of sites in hospitals (range, 28.4%–39.7%) and 46.3% of sites in outpatient clinics (range, 7.4%–82.8%). Conclusions: Surfaces in hospitals outside patient rooms and in outpatient facilities are frequently contaminated with healthcare-associated pathogens. Improvements in cleaning and disinfection practices are needed to reduce contamination.